Silica Nanostructures Produced Using Diatom Peptides with Designed Post‐Translational Modifications. (3rd June 2020) - Wallace, Andrea K.; Chanut, Nicolas; Voigt, Christopher A.
Abstract: Diatoms produce intricately patterned silica structures under ambient conditions, a process initiated by post‐translationally modified silaffin peptides that nucleate silicic acid. Designing these peptides would enable the production of silica nanostructures with desired properties; however, the functional effects of modifications are poorly understood. Here, Escherichia coli is used to express and modify recombinant silaffin R5 peptide from the diatom Cylindrotheca fusiformis . A library of 38 enzymes is tested for R5 modifications in vitro, from which active methyltransferases, kinases, acetyltransferases, oxidases, and myristoyltransferases are identified from diatoms, humans, yeast, and bacteria. Modified R5 peptides are used for silica precipitation and the impacts on particle size, shape, porosity, and surface area are quantified. In vivo pathways are designed to coexpress R5 and a modifying enzyme and the resulting peptide is used to nucleate silica nanostructures with controlled size (100–3500 nm), porosity (20–635 m 2 g −1 ), or embedded with melanin. It is found that phosphorylation reduces the need for inorganic phosphate during silica synthesis. The simultaneous methylation and phosphorylation of R5 leads to smaller particles requiring less inorganic phosphate. Inspired by diatoms, the use of post‐translationally modified peptides will enable the control of silica morphology under ambient conditions, with potential applications in electronics and photonics. Abstract : Diatoms build tiny silica structures under ambient conditions with intricate structural and optical properties. Here, the diatom peptide (R5) is produced in E. coli with enzymes from many sources, including humans, that modify the peptide structures. These are found to precipitate silica into structures of diverse size, shape, surface area, and porosity that have applications spanning photonics to catalysis.